Multifactorialas decisivefactor for the regionalsecurity system in Central Asia (International relations and international law Journal, 2016)
The article is devoted to analysis the regionalsecurity system in Central Asia. Due to the geopoliticaland geo-economic characteristics Central Asia is the subject of world politics and the countries of theregion are heavily exposed to the external influence of the leading world powers. External factors remaindominant in the modern strategy of the Central Asian region. Russia, China, the USA, the European Unionare the dominant factors that determine both the structure of regional international system and foreignpolicy priorities of Central Asia countries. Different levels of influence of external actors reinforce andsupport multifactorial of the region. A multifactorial itself is a subject to instability, amorphousness andunpredictability of regional safety system.
Keywords: regionalsecurity system; Central Asian Union; Organization of Collective Security Treaty Shanghai Cooperation Organization; Conference on Interaction and Confidence-Building Measures in Asia